Distribution and Damage Potentials of Tomato Leafminer, Tuta absoluta (Lepidoptera: Gelechiidae) Sindh, Pakistan - Abdul Hayee Gabol; Arfan Ahmed Gilal; Lubna Bashir Rajput; Jamal-U-Ddin Hajano; Ghulam Qader Mangrio (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
Tomato leafminer (TLM), Tuta absoluta (Lepidoptera: Gelechiidae), is a serious oligophagous pest of tomatoes. Although originated in South America, it has now been introduced and spread in almost all the tomato-growing areas of the globe. Therefore, studies were undertaken to determine the infestation of T. absoluta on tomato parts at various locations of six main tomato growing areas of Sindh i.e., Badin, Thatta, Mirpur Khas, Hyderabad, Sanghar and Shaheed Benazirabad. Five tomato fields (locations) were randomly selected from each district to determine the infestation of TLM based on its characteristic mines on tomato leaves and fruits. Tuta absoluta infestation was recorded on tomato leaves and fruits observed at all the sampling locations of six districts with significant differences among plant parts, locations, and districts. The highest infestation on leaves (19.36±0.92 %) and fruits (1.36±0.28 %) was observed from location one of Mirpur Khas district. District-wise, overall, the highest infestation of T. absoluta on tomato leaves (17.04±0.38 %) and stems (1.10±0.11 %) was recorded at Mirpur Khas, whereas Shaheed Benazirabad and Hyderabad districts suffered the lowest infestation on leaves (4.18±0.22 %) and fruits (0.26±0.04 %), respectively. The highest infestation of T. absoluta at Badin (14.10±0.28 %), Thatta (11.10±0.27 %), Sanghar (8.22±0.34 %), Hyderabad (5.32±0.18 %) and Shaheed Benazirabad (4.18±0.22 %) was also recorded on leaves. Therefore, early monitoring and management should be taken by growers to restrict the losses of T. absoluta on tomatoes, whereas government should adopt strict quarantine measures on the movement of tomato nurseries to restrict its spread.